Conservative Treatment of Degenerative Meniscus: Building Consensus for the Development of a Rehabilitation Program - Páscoa Pinheiro, João; Rovisco Branquinho, Lurdes; Pinheiro, Joana; Ramos, Susana (International Journal of Innovative Research in Medical Science, 2024)
Background: Degenerative meniscus is a common condition, and the current therapeutic approaches lack consistency, leading to uncertain outcomes. The aim is to establish a standardized approach for the conservative management of degenerative meniscus, informed by evidence-based practices and expert input from professionals in related areas. Methods: The rehabilitation program was developed through a multidisciplinary approach. A systematic review of the existing literature on degenerative meniscus treatments was conducted to identify evidence-based practices. Additionally, experienced professionals from Rehabilitation Medicine, Orthopaedics, and Physiotherapy were consulted to provide their insights and expertise. Consensus meetings were held to integrate these diverse perspectives into a comprehensive rehabilitation program. Results: The resulting rehabilitation program for degenerative meniscus offers a structured and evidence-based approach. It includes a combination of exercises, physical modalities, and lifestyle modifications tailored to the individual patient's needs. Key components of the program focus on muscles strengthening, improving joint stability, and reducing pain and inflammation. The program also emphasizes patient education to promote long-term self-management. Conclusions: By bringing together experts from various healthcare disciplines and incorporating evidence-based strategies, this rehabilitation program addresses the current lack of coherence and heterogeneity in degenerative meniscus treatment. It provides a standardized and functional approach to conservative management. The program's emphasis on individualized care and patient education may lead to better treatment adherence and outcomes. Furthermore, collaboration among healthcare professionals ensures a well-rounded and comprehensive approach to addressing the multifaceted nature of degenerative meniscus.